2005
DOI: 10.3200/genp.132.2.187-204
|View full text |Cite
|
Sign up to set email alerts
|

Mice Selectively Bred for Open-Field Thigmotaxis: Life Span and Stability of the Selection Trait

Abstract: In 2 experiments, the authors examined 69 mice selectively bred for high or low levels of open-field (OF) thigmotactic behavior (high open-field thigmotaxis [HOFT] and low open-field thigmotaxis [LOFT], respectively). They found that the strains differed in defecation during the 60-min exposure to the OF. Furthermore, the strains differed with regard to their life spans: The more thigmotactic HOFT mice lived longer than the LOFT mice. The strains were not differentiated by food intake or excretion. The strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The regularity in which a MDF is managed and exhausted before passing to the next MDF implies recordkeeping and therefore cognition-related skills. The primacy of attention to edges over attention to the spaces between them is characteristic of perceptual systems, regardless of the agent and the sensory channel used (35)(36)(37)(38). The recent discovery of border cells in the rat's entorhinal cortex (39) supports the distinct status of borderline movement, while the sequence we report suggests a corresponding developmental dynamics in the brain.…”
Section: Discussionsupporting
confidence: 51%
“…The regularity in which a MDF is managed and exhausted before passing to the next MDF implies recordkeeping and therefore cognition-related skills. The primacy of attention to edges over attention to the spaces between them is characteristic of perceptual systems, regardless of the agent and the sensory channel used (35)(36)(37)(38). The recent discovery of border cells in the rat's entorhinal cortex (39) supports the distinct status of borderline movement, while the sequence we report suggests a corresponding developmental dynamics in the brain.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, increased latency to first entry in the anxiogenic areas of the EPM (open arms) and of the open field arena (central zone) were observed, together with decreases in the distance traveled in these areas. Moreover, thigmotaxis, a stable and robust indicator of discomfort manifested by the tendency to remain close to the walls (secure area) [ 39 40 ] was markedly increased in artificial daylight–exposed, as indicated by increases in the number of activities close to walls in all the behavioral tests performed. Besides, a shift in behavioral baseline was indicated by increases in EPM central platform time [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 10 attributes chosen for this study (Table 2) consist of the variables found most useful for the analysis of open-field behavior throughout many previous studies. The distance from the wall d was shown to measure heritable thigmotactic behavior (Broadhurst, 1975;Leppanen et al, 2005;Lipkind et al, 2004) highly replicable across laboratories . The momentary speed v was shown to be a key variable in the intrinsic categorization of behavior into progression and 'lingering' in both mice ) and rats (Kafkafi et al, 2001).…”
Section: Pattern Array Analysismentioning
confidence: 99%
“…Thus the key to applying a data mining approach in behavioral analysis is designing a useful 'chip', that is, constructing a proper categorization of the data into multiple types of behavior that can be mined. To this end the units employed by PA consist of a large number (B100 000) of complex movement patterns, algorithmically defined as simultaneous combinations of several ethologically relevant 'attributes' such as the distance from the arena wall (Broadhurst, 1975;Leppanen et al, 2005;Lipkind et al, 2004), the speed and acceleration of movement (Kafkafi et al, 2003b), direction of movement (Horev et al, 2007), and turning . For example, by using the three attributes of acceleration, distance from the wall and turning, a specific movement pattern in PA may be defined as the combination 'heavily braking while moving near the wall but turning slightly away from it'.…”
Section: Introductionmentioning
confidence: 99%